Clinical and parasitological features of Leishmania infection among gold miners in the Oiapoque basin, an international Brazil-French Guiana border. - Pamela Mosquera Atehortua; Amanda Figueira da Silva; Lohaine Mafra; Samyra Almeida-da-Silveira; Cintia Xavier De Mello; Hermano Gomes Albuquerque; Lucas André Boaventura de Carvalho; Louise Hureau-Mutricy; Maylis Douine; Alda Maria Da-Cruz; Martha C Suárez-Mutis; Adriano Gomes-Silva (PLoS Neglected Tropical Diseases, 2024)
Gold miners working illegally in mines live in poor health conditions related to their strenuous work and precarious housing. Therefore, they are at higher risk for infectious diseases. American tegumentary leishmaniasis (ATL) appears to be of great concern to the population living in the Guiana Shield region. Our aim was to describe their demographic characteristics, the clinical features of cutaneous leishmaniasis (CL), and the frequency of Leishmania infection in people working in illegal gold mines in French Guiana. A cross-sectional study was carried out from October to December 2019 in Oiapoque city, Amapá, Brazil. Indeed, many gold miners working in French Guiana are originally from Brazil, and from Oiapoque in particular. A total of 105 participants from 31 different mining sites in French Guiana were recruited. Suspected Leishmania infection was confirmed by the following: detection of kDNA in blood or the lesion site; detection of specific antibodies; or detection of IFN-γ release after blood incubation with leishmanial antigens (IGRA-Leish). Nine active CL cases, 38 healed ATL (hATL) and 58 cases with no history of ATL (noATL), were identified. Only half of the treated hATL (50.0%; n = 14) reported having been assisted by a health care unit and the others treated themselves. PCR-kDNA for Leishmania was positive in the blood of 100% of CL cases. Curiously, blood PCR-kDNA was positive in 13% of hATL patients and in 15.5% of noATL patients. The IGRA-Leish was positive in 60.5% of hATL and in 37.9% of noATL. In addition to scars suggestive of CL, 71% of hATL had laboratory evidence of Leishmania infection. Restriction fragment polymorphism (RFLP) of the hsp70 gene identified a sympatric circulation of L. (V.) guyanensis (n = 4), L. (V.) braziliensis (n = 1), L. (L.) amazonensis (n = 2), L. (V.) shawi (n = 1) and L. (V.) naiffi/shawi (n = 1). Taking the laboratory techniques and the clinical evaluations together, 76% (n = 80) of the 105 participants had evidence of Leishmania infection. These results suggests that illegal gold miners working in French Guiana are at high risk for infection with different species of Leishmania, but their illegal condition and remoteness make it difficult for them to access health services.